2022
DOI: 10.3389/fcvm.2022.935333
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer, BNP/NT-pro-BNP, and creatinine are reliable decision-making biomarkers in life-sustaining therapies withholding and withdrawing during COVID-19 outbreak

Abstract: BackgroundThe decision for withholding and withdrawing of life-sustaining treatments (LSTs) in COVID-19 patients is currently based on a collegial and mainly clinical assessment. In the context of a global pandemic and overwhelmed health system, the question of LST decision support for COVID-19 patients using prognostic biomarkers arises.MethodsIn a multicenter study in 24 French hospitals, 2878 COVID-19 patients hospitalized in medical departments from 26 February to 20 April 2020 were included. In a propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…However, decreased lymphocyte count was commonly observed in our cohort, which is consistent with previous studies (16). Our results indicated that COVID-19 patients with eosinopenia had higher levels of procalcitonin, which has recently been identified as a predictor of severity in hospitalized COVID-19 patients (21). A previous study suggested that high levels of B-type natriuretic peptide (BNP), a marker of heart failure, were significantly higher in the eosinopenia group, which is consistent with previous reports suggesting its importance in treatment decision-making for COVID-19 patients (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, decreased lymphocyte count was commonly observed in our cohort, which is consistent with previous studies (16). Our results indicated that COVID-19 patients with eosinopenia had higher levels of procalcitonin, which has recently been identified as a predictor of severity in hospitalized COVID-19 patients (21). A previous study suggested that high levels of B-type natriuretic peptide (BNP), a marker of heart failure, were significantly higher in the eosinopenia group, which is consistent with previous reports suggesting its importance in treatment decision-making for COVID-19 patients (22).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, high levels of B-type natriuretic peptide (BNP), a marker of heart failure, were significantly higher in the eosinopenia group, which is consistent with previous reports suggesting its importance in treatment decision-making for COVID-19 patients (21). Furthermore, we found that laboratory biomarkers associated with the diagnosis and prognosis of COVID-19 patients, including glutamic oxaloacetic transaminase, serum creatinine, blood urea nitrogen, lactate dehydrogenase, creatine kinase, creatine kinase MB, myoglobin, and troponin I, were significantly higher in the eosinopenia group compared to the normal eosinophil group (22).…”
Section: Discussionsupporting
confidence: 90%
“… 33 BNP and NT-pro BNP are well-known markers of heart failure for the detection of left ventricular hypertrophy and left ventricular systolic dysfunction. 34 , 35 The serum levels of BNP and NT-pro BNP will increase in chronic congestive heart failure. ISO treatment induces myocardial injury, which may ultimately lead to myocardial necrosis, left ventricular hypertrophy, and heart failure.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical variables such as D-dimer [ 38 ], procalcitonin [ 39 ], glucose [ 40 ], creatinine [ 41 ], and urea [ 42 ] have demonstrated an association with coagulation pathways and lung, kidney, and liver damage, which could lead to more severe disease and death in COVID-19 patients. Upregulated miR-21-5p expression levels were statistically correlated with procalcitonin, creatinine, urea, and thromboplastin-D-dimer index in non-survivor patients; albumin, D-dimer, and ferritin levels were correlated in the whole population.…”
Section: Discussionmentioning
confidence: 99%